Del tabú a la sacralidad: la menstruación en la era del sagrado femenino = From taboo to sacredness : menstruation in the age of the sacred feminine - Ramírez Morales, María del Rosario (Ciencias sociales y religión, 2016)
Menarche as the moment which the women’s body acquires its fertility character has been appreciated by different cultures as one of the main female rites of passage, but also as the beginning of a series of reviews, mostly negative, towards women and their periodic bleeding. However, from the spiritual perspective of the sacred feminine, the redefinition of menstruation arises through the use of symbolic components which, rather than classifying blood as an element of potential danger, is considered as an essential fluid emanating from a goddess woman. Thus, this paper analyzes the links that are generated between the approach of the sacred feminine, menstruation and the forms that it takes from the consideration of the body as a privileged space of significance.